(untitled) (Revista de Investigaciones Universidad del Quindío, 2020)
Objective: The main objective of this research is to obtain bacteria of the genus Pseudomona spp. with biodegrading capacity of hydrocarbons in surface water samples from the Bay of Cartagena de Indias. Material and Method: Observational, descriptive, cross-sectional and prospective design. Three samples of surface water were taken from the Bay of Cartagena de Indias, they were sown for pre-adaptation and biological adaptation of the bacteria in a medium with mineral salts, ACPM 1% v/v and crude oil 1% v/v, as the only carbon source. and energy. Results: The bacteria that grew in the media with crude oil were identified in 31 morphotypes of bacterial colonies, of which only 19.4% were positive for the presence of Pseudomona spp., And the remaining 80.6%, belonging to other bacterial groups. Discussion: A color change in the nutrient agar was evidenced during the isolation procedure of the bacteria from sample 2 related to the presence of Pseudomonas species, especially P. aeruginosa. Conclusion: The presence of the genus of Pseudomona spp. with oil biodegrading capacity in one of the water samples collected in the Bay of Cartagena. This study opens the possibility of future work on bioprospecting and metabolic identification of the isolated strains.